Megaselia scalaris (Diptera : Phoridae) causing myiasis in Crotalus durissus terrificus (Serpentes : Viperidae) in Brazil - Silva, R. J. da [UNESP]; Prado, A. P. do; Rodrigues, R. R.; Lopes, C. A. D.; Godoy, W. A. C. (Amer Entomol Soc, 1999)
We describe a case of myiasis in Crotalus durissus terrificus (Laurenti) caused by Megaselia scalaris (Loew). The snake was Found in Anhembi, São Paulo, Brazil, with a lesion measuring 25 mm in diameter where the larvae of M. scalaris had penetrated the ribs. The opportunistic behavior of the larvae of M. scalaris is discussed.
Keywords: Megaselia scalaris; Crotalus durissus terrificus; Phoridae; myiasis; Serpentes; Viperidae